Transtibial prosthetic suspension: less pistoning versus easy donning and doffing - Gholizadeh, H.; Abu Osman, Noor Azuan; Eshraghi, A.; Ali, S.; Sævarsson, S.K.; Wan Abas, Wan Abu Bakar; Pirouzi, G.H. (2012)
Poor suspension increases slippage of the residual limb inside the socket during ambulation. The main purpose of this article is to evaluate the pistoning at the prosthetic liner-socket interface during gait and assess patients' satisfaction with two different liners. Two prostheses with seal-in and lock-ing liners were fabricated for each of the 10 subjects with transtibial amputation. The Vicon motion system was used to measure the pistoning during gait. The subjects were also asked to complete a Prosthesis Evaluation Questionnaire. The results revealed higher pistoning inside the socket during gait with the locking liner than with the seal-in liner (p < 0.05). The overall satisfaction with the locking liner was higher (p < 0.05) because of the relative ease with which the patients could don and doff the device. As such, pistoning may not be the main factor that determines patients' overall satisfaction with the prosthesis and other factors may also contribute to comfort and satisfaction with prostheses. The article also verifies the feasi-bility of the Vicon motion system for measuring pistoning dur-ing gait.